Bio-controlled health evaluation of brown-marbled grouper against vibriosis - Mohamed Alipiah, Norfarrah; Ramli, Nur Hasli Syahidda; Shamsudin, Mariana Nor (2012)
The rapid expansions of aquaculture industry are dependent to a large extent on the availability of healthy fingerlings. Currently mortality rates are high as their adaptive immunity is not fully developed against potential pathogens and diseases such as in Vibriosis. The situation warrant for alternative treatment approaches possibly with low impact on human, animals and the environments. This study evaluated an approach involving the modulation of ecosystem microbiota to elevate fish immune system against diseases. The research hypothesized that associated bacterial loads influence the host immunity and the associated bacteria also produced antibacterial substances in order to compete with other surface colonizers. The marine isolate showed inhibitory activity against vibriosis pathogens V. harveyi and V. parahaemolyticus. In the challenge experimental test on Brown-marbled grouper fingerlings, it was observed that the fingerlings treated with marine isolates have lower survival rate. The unexpected observation could be due to the possibility that the marine isolates are opportunistic microbes which kill the fingerlings when the latter are expose to diseases. A thorough study will be conducted in future experiments on antibody produced during the treatment together with detailed disease symptom observations to provide a better understanding the interaction between the marine isolates and challenged fingerlings.